Analisis Efektivitas Pembelajaran Al-Qur'an Hadits dalam Meningkatkan Antusiasme Siswa di MA Nihayatul Amal Rawamerta Karawang - Azizah Haya Dzakiya; Anne Setiawati; Diyani; Maya; Muhamad Hafidz Wahyudin; Muhammad Faisal Arrayan (Cv. Kayaswara, Indonesia, 2025)
This research was conducted at MA Nihayatul Amal Rawamerta Karawang because the Al-Qur'an Hadith learning method is interesting and effective in increasing student enthusiasm. It aims to describe the implementation of Al-Qur'an Hadith learning in formal education environments, as well as evaluating its effectiveness in instilling Islamic values ​​​​in students. The method used is a descriptive qualitative approach with observation, interviews and documentation. The results of the study indicate that varied learning methods, contextual media and support facilities such as libraries can increase student enthusiasm. However, there are still obstacles such as lack of resources and minimal direct involvement of the principal. Therefore, the implementation of learning the Al-Quran Hadith in this school has been going quite well, but there needs to be a solution to deal with obstacles in learning the Al-Quran Hadith.